2012
DOI: 10.1254/jphs.12007sc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinally Administered Simvastatin on the Formalin-Induced Nociceptive Response in Mice

Abstract: Statins are widely prescribed for treatment of hyperlipidemia. Statins lower plasma cholesterol levels through the inhibition of 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase. Several large clinical trials indicated that statins reduce the morbidity and mortality of coronary artery disease and the incidence of stroke (1). These pleiotropic effects of statins are considered to result from their actions other than lipid lowering, since the overall clinical benefits of statin therapy appeared to be greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Repeated treatment with simvastatin and rosuvastatin also pro duced an antihyperalgesic effect in mice and rats with nerve injuryinduced neuropathic pain (18). Recently, we also reported that intrathecal, but not intracerebroven tricular, administration of simvastatin exerted an antino ciceptive effect in formalininduced nociception (19). In contrast to these studies, our present results obtained using an oxaliplatininduced neuropathic pain model showed that neither simvastatin nor atorvastatin pro duced any antihyperalgesic or antiallodynic effects.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Repeated treatment with simvastatin and rosuvastatin also pro duced an antihyperalgesic effect in mice and rats with nerve injuryinduced neuropathic pain (18). Recently, we also reported that intrathecal, but not intracerebroven tricular, administration of simvastatin exerted an antino ciceptive effect in formalininduced nociception (19). In contrast to these studies, our present results obtained using an oxaliplatininduced neuropathic pain model showed that neither simvastatin nor atorvastatin pro duced any antihyperalgesic or antiallodynic effects.…”
Section: Discussioncontrasting
confidence: 92%
“…Systemic treatment with the lipidlowering drugs simvastatin and rosuvastatin attenuates thermal hyperal gesia and mechanical allodynia in nerveligated rats (18). We recently reported that intrathecal treatment with simvastatin attenuated the second, but not first, phase of the formalininduced nociceptive response, suggesting inhibition of the sensitization of spinal nociceptive trans mission (19). Therefore, these drugs are also expected to relieve the acute sensory paresthesias induced by oxaliplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ohsawa et al (2012) suggest that simvastatininduced antinociception is mediated by attenuation of the sensitization of spinal nociceptive transmission. On the other hand, it is known that statins inhibit the synthesis of isoprenoids, including RhoA GTPase, which may contribute to the development of opioid tolerance and dependence (Goldstein and Brown, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure used was similar to that described previously [10]. Twenty microliters of 2.5% formalin solution (95% formaldehyde) were injected intraplantarly (i.pl.)…”
Section: Methodsmentioning
confidence: 99%